The Effectiveness of Virtual Reality Media on Primary School Students' Learning Outcomes - Erviana, Vera Yuli; Sepriansyah, Y (Universitas Pendidikan Ganesha, 2024)
The development of technology today has not been fully followed by various fields of human life, one of which is the world of education. There are still problems faced such as low student learning outcomes, this factor is due to some teachers not fully utilizing technology in the learning process. This study aims to analyze the effectiveness of virtual reality media on the learning outcomes of elementary school students. The type of research used in this study is quantitative with experimental methods. The type of experimental research used in this research is a Pre-Experimental Design with One-Group Pretest-Post-test type. The data collection techniques used were observation, tests, and documentation. The data analysis technique used was descriptive analysis and prerequisite test analysis. The results of this study obtained Pretest scores with an average score of 65.07. Then obtained an average Post-test of 86.03. From the results of the T-test conducted, significant results were obtained. This is evidenced by the Sig. (2- 2-tailed) of 0.000, where the Sig. value is <0.05, so Ha is accepted and Ho is rejected Based on the results obtained, it can be concluded that virtual reality media is effective on student learning outcomes.